THE STUDY OF SYNTETIC PEPTIDE LOADED PLGA NANOPARTICLES CYTOTOXICITY IN VITRO - Derman, Serap; Akdeste, Zeynep Mustafaeva; Ates, Sezen Canim; Mansuroglu, Banu; Kizilbey, Kadriye; Bagirova, Melahat; Allahverdiyev, Adil (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2017)
Canine parvovirus (CPV) is a viral disease which is seen widely worldwide and infects puppies. Current vaccines which developed against this infection have several disadvantages. The antigenic property of different peptide sequences on VP2 capsid protein which belongs to CPV has been shown in different studies. However, carriers or adjuvants are also required for peptide antigens which have small molecular size and weak immunogenicity. Recently, nanoparticulate vaccine studies have begun against variety of infectious diseases. But, there is no vaccine study based on nanoparticle in CPV infections. In this study, cytotoxicity of W-1L19 peptide loaded poly(lactide-co-glycolide) (PLGA) nanoparticle systems was examined for the first time on mouse fibroblast L929 cell lines. A microculture tetrazolium salt reduction assay was used to determine the cellular toxicity of the CPV W-1L19 synthetic peptide and PLGA nanoparticles [empty (NP1), peptide loaded (NP2) and peptide+FITC dye loaded (NP3)]. The obtained results showed that the toxicity of free peptide is enhanced by loading to biocompatible PLGA nanoparticles. For the first time in this study it is shown that W-1L19 peptide loaded PLGA nanoparticle systems are non-toxic. Thus, these results suggest that it is possible for use these nanoparticular system as a vaccine candidate in future.
Keywords: Canine parvovirus; poly(lactide-co-glycolide) nanopartides; L929 cell line; in vitro cytotoxicity; PLGA; VACCINE; DOGS; Environmental Sciences & Ecology